Food Systems for an Urbanizing World - Tefft, James; Jonasova, Marketa; Adjao, Ramziath; Morgan, Anjali (World Bank, Washington, DC and Food and Agriculture Organization of the United Nations, 2019)
The report is organized into seven chapters, as follows, with additional text supported by data in the annexes: this first chapter sets out the context for the report, presents the objectives, outlines the methodology and approach, and briefly introduces the scope and organization. Chapter two looks at the key drivers and underlying trends that are already shaping the agenda or will influence the future of urban food issues. Chapter three pulls together relevant data and information to describe the structure and performance of the three interrelated channels in urban food system, traditional, modern and informal, the latter catering primarily to the urban poor. Chapter four introduces the transform framework of the interlinked food system outcome areas related to job creation, affordability and accessibility, security and nutrition, and sustainability and resilience. It also discusses an initial typology of cities based on demographic and food system criteria with which to begin to consider priority interventions. Chapter five discusses the enabling conditions of the transform framework: Transformative institutions; facilitating and progressive policies; Open data, knowledge and evidence base; Resources for effective public and private financing; and multistakeholder governance mechanisms and capacity. Chapter six examines four broad areas of intervention to achieve results in the interlinked outcome areas: Remunerative jobs and better agribusinesses; affordability and accessibility for food security; nutritious, diverse, quality and safe food; and sustainable, resilient agriculture and food systems. An initial set of indicative interventions and entry points are presented for each area, with further refinement and precision to be determined by analysis and consultation in subsequent phases. Finally, chapter seven synthesizes the salient findings and proposes a streamlined and succinct approach for advancing this important agenda, including potential instruments and program sequencing, key information and data gaps, and partnership opportunities.